Shooter - Myers, Walter Dean, 1937- (New York : HarperTempest, 2005)
Teachers, therapists, law enforcement officials, and others try to piece together the facts in the aftermath of a tragedy in which Len, a high school senior fed up with being bullied, shoots and kills a football hero and then commits suicide.
"Amistad.".
Booklist starred.
School Library Journal.
Wilson's Senior High School.
Booklist starred, February 2004.
Bulletin of the Center for Children's Books starre, June 2004.
Keywords: Bullying -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Emotional problems of teenagers -- Juvenile fiction; High schools -- Juvenile fiction; School violence -- Juvenile fiction; Bullies -- Fiction; Emotional problems -- Fiction; Family problems -- Fiction; School violence -- Fiction; Schools -- Fiction; Bullies -- Fiction; Emotional problems -- Fiction; Family problems -- Fiction; School stories; School violence -- Fiction